Fracturas del tercio superior facial. Experiencia en el Servicio de Cirugía de Cabeza, Cuello y Máxilo-Facial del Hospital Nacional “Dos de Mayo”, 1999 – 2009 - Avello Canisto, Francisco (2014)
Introduction: Superior third facial fractures represent an important but rare pathology in the specialty of head, neck and maxillofacial surgery, and result from severe trauma. Objectives: To determine the presentation of superior third facial fractures by age, sex, causal agent and classification. Design: Observational descriptive study. Setting: Head, Neck and Maxillofacial Surgery Service, Dos de Mayo National Hospital, Lima, Peru. Participants: Patients with superior third facial fracture. Methods: Medical records data between June 1999 and May 2009 were captured. Main outcome measures: Age, sex, causing agent and classification. Results: Forty nine patients were included, Ninety pe cent were male, about two thirds (67.5%) were between 21 and 40 years old. More than half of the lesions (55%) resulted from traffic accidents and 23% from robberies; more than 40% had superior third fractures only and 59% were accompanied by midface fractures. Conclusions: Superior third facial fractures are important in the facial region. Clinical diagnosis depends on the affected structure. Treatment should be timely to prevent sequelae and complications. Traffic injuries and robberies are increasingly important causes. This study would contribute to developing treatment protocols in emergency services.